Criminal Protection of the Environment in Jordanian Legislation - ALKSEILAT, Abdullah; ABU ISSA, Hamzeh; AL-REFOU, Ayman (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).01, 2020)
Having a clean and pollution-free environment is one of the most important rights of humans. Such a right has been recognized by national and international covenants, so laws have been devoted to protecting them and preventing infringement of their components and elements, because of the importance they constitute at the level of human life. As a result of the increasing assault on the environment and the gravity of the infringement of its elements, the legislator intervened in all countries (including the Jordanian legislator), to lay down the rules regulating the protection thereof and punishing the perpetrators of environmental crimes through deterrent measures and appropriate penalties. Therefore, this research will shed light on the criminal provisions decided by the Jordanian legislator in the Environmental Protection Law No. 6 of 2017, especially in terms of the penalties decided by the legislator on the perpetrators of environmental crimes, with the aim of embodying the criminal and legal protection of the environment. As the aim of this article is to clarify and clarify the position of the Jordanian legislator regarding the penal protection of the environment, we have used the descriptive and analytical approach to reach the results. The article concluded that the Environmental Protection Law stipulated several crimes to protect the environment in its various forms, but the legislator did not put in place precautionary measures prior to the occurrence of the crime, and on the other hand, the provisions laid down by the legislator are still scattered and need a general rooting for all environmental crimes.